2012
DOI: 10.1021/cb3002478
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Luciferase Reporter from a Deep Sea Shrimp Utilizing a Novel Imidazopyrazinone Substrate

Abstract: Bioluminescence methodologies have been extraordinarily useful due to their high sensitivity, broad dynamic range, and operational simplicity. These capabilities have been realized largely through incremental adaptations of native enzymes and substrates, originating from luminous organisms of diverse evolutionary lineages. We engineered both an enzyme and substrate in combination to create a novel bioluminescence system capable of more efficient light emission with superior biochemical and physical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
1,490
3
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,333 publications
(1,592 citation statements)
references
References 35 publications
(76 reference statements)
22
1,490
3
7
Order By: Relevance
“…S2). Ataluren treatment of mammalian 293H cells stably transfected with wild-type (WT) or PTC(W12X)-containing NanoLuc (19) reporters promoted a bell-shaped dose-response, with a peak ninefold increase in luciferase activity derived from the PTC reporter at 10 μM (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). Ataluren treatment of mammalian 293H cells stably transfected with wild-type (WT) or PTC(W12X)-containing NanoLuc (19) reporters promoted a bell-shaped dose-response, with a peak ninefold increase in luciferase activity derived from the PTC reporter at 10 μM (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Procedures for RNA analysis, protein purification, and luciferase assays were as described previously (3,19,21,38) or in SI Appendix. Western analyses and protein purification largely used antibodies or affinity resins targeted to the HA, FLAG, StrepII, T-GFP, and 6× His epitope tags expressed from the respective reporter constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Our study used NanoLuc as a reporter for the evaluation, as it is the most highly luminescent luciferase and provides 150-fold brighter bioluminescence than firefly luciferase. 17) In other words, the detection limit of our NanoLuc assay is sub pM, which is at least 1000-fold more sensitive than the ELISA used in the published reports.…”
Section: Discussionmentioning
confidence: 83%
“…17) In addition, to locate L. lactis in the tissues, we performed an ex vivo analysis using fluorescence-labeled L. lactis, and found that L. lactis accumulated in the Peyer's patches (PPs) irrespective of mInlA expression. Our observations suggested that DNA transfer from L. lactis occurred predominantly in the PPs not in the intestinal epithelial cells.…”
mentioning
confidence: 99%
“…This time the reporter was generated with Nano-luciferase (nLUC) that is smaller in size and thus more sensitive in cellular responses compared to firefly-luciferase (Hall et al, 2012). To substantiate this splicing assay, evolutionarily conserved splicing sites of the intron in gHSFA3 were mutated to be unspliced at splice donor (Do) or acceptor (Ac) site (Fig.…”
Section: Sta1 Function In Pre-mrna Splicingmentioning
confidence: 99%